1990
DOI: 10.1016/0020-7292(90)90173-i
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum total cortisol levels in normal and pathologic pregnancies

Abstract: The effect of pregnancy on maternal serum total cortisol (MSFT) was studied systematically in the course of 90 normal pregnancies (n = 204). Moreover, the evaluation of MSFT determinations in abnormal pregnancies, intrauterine growth retardation (IUGR) and obstetrical complications, premature rupture of the membranes (PROM), premature delivery (PD), and full term pregnancies with post maturity syndrome (PMS) were also investigated. MSFT was measured by an enzyme immunoassay. Gradual increase in MSFT was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The varied times of data collections may also explain the inconsistent findings. Some studies used blood (Erickson et al, 2001;Phocas et al, 1990;Hobel et al, 1999;Mazor et al, 1994Mazor et al, , 1996Ruiz et al, 2001) to measure the cortisol level whereas a few studies measured cortisol in urine (Diego et al, 2009;Field et al, 2004Field et al, , 2006 and one study used hair to measure cortisol (Kramer, et al, 2009) and two studies used saliva (Harville et al; Obel et al). Cortisol levels can be detected in blood, urine, and saliva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The varied times of data collections may also explain the inconsistent findings. Some studies used blood (Erickson et al, 2001;Phocas et al, 1990;Hobel et al, 1999;Mazor et al, 1994Mazor et al, , 1996Ruiz et al, 2001) to measure the cortisol level whereas a few studies measured cortisol in urine (Diego et al, 2009;Field et al, 2004Field et al, , 2006 and one study used hair to measure cortisol (Kramer, et al, 2009) and two studies used saliva (Harville et al; Obel et al). Cortisol levels can be detected in blood, urine, and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a number of researches examined the relationship between stress, depression and preterm birth without considering cortisol (Copper et al, 1996;Dole et al, 2003;Jesse, Swanson, Newton, & Morrow, 2009;Jesse, Seaver, & Wallace, 2003;Wadhwa, Culhane, Vitgina, Brave et al, 2001;Khashan et al, 2009;Whitehead et al, 2002;Zhu et al, 2010). Two studies examined the relationship between stress and cortisol only (Harville et al, 2009;Obel et al, 2004) while five studies only explored the relationship between cortisol and preterm birth (Campbell, Challis, DaSilva, & Bocking, 2005;Phocas, Sarandakou, & Rizos, 1990;Mazor et al, 1994Mazor et al, , 1996Sandman et al, 2006). Of the 22 articles seven determined the relationship between stress or depression, cortisol and preterm birth together at the same time (Diego et al, 2009;Erickson et al, 2001;Field et al, 2004Field et al, , 2006Hobel et al, 1999;Kramer et al, 2009;Shaikh et al, 2011).…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, animal studies are typically designed to expose the foetus to antenatal steroids during a normal gestation progressing to an undisturbed normal term delivery. In contrast, preterm infants are exposed to antenatal steroids during threatened preterm labour, a time of heightened maternal and foetal stress with high levels of endogenous maternal and foetal glucocorticoids, peaking during preterm delivery (23,24). Exogenous steroids given on top of already high levels of endogenous glucocorticoids may not produce additional long-term effects on the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Under a state of chronic stress, the regulatory mechanisms of the stress response fail, leading to changes in cortisol levels 9. Some researchers suggest higher levels of acute stress are associated with higher levels of cortisol, a biological marker of stress, in pregnant women1315 and that elevated maternal cortisol levels are related to preterm birth 1618. A recent review of 15 studies examining the relationship between cortisol and PTB revealed that the majority of studies reported a relationship between maternal cortisol levels and PTB.…”
Section: Introductionmentioning
confidence: 99%